Reactive astrogliosis in the dentate gyrus of mice exposed to active volcanic environments - Navarro-Sempere, Alicia (2021)
Air pollution has been associated with neuroinflammatory processes and is considered a risk factor for the development of neurodegenerative diseases. Volcanic environments are considered a natural source of air pollution. However, the effects of natural source air pollution on the central nervous system (CNS) have not been reported, despite the fact that up to 10% of the world’s population lives near a historically active volcano. In order to assess the response of the CNS to such exposure, our study was conducted in the island of Sao Miguel (Azores, Portugal) in two different areas: Furnas, which is volcanically active one, and compared to Rabo de Peixe, a reference site without manifestations of active volcanism using Mus musculus as a bioindicator species. To evaluate the state of the astroglial population in the dentate gyrus in both samples, the number of astrocytes was determined using immunofluorescence methods (anti-GFAP and anti-GS). In addition, the astrocytic branches in that hippocampal area were examined. Our results showed an increase in GFAP+ astrocytes and a reduction in GS+ astrocytes in Furnas-exposed mice compared to animals from Rabo de Peixe. In addition, astrocytes in the dentate gyrus of chronically exposed animals exhibited longer branches compared to those residing at the reference site. Thus, reactive astrogliosis and astrocyte dysfunction are found in mice living in an active volcanic environment.